Enhancing Food Self-Sufficiency Through the SIPULUNG Sack-Based Sweet Potato Cultivation System in Bandulan, Malang - Estiasih, Teti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2026)
Bandulan Village in Malang City faces limited agricultural land, leaving local resources such as sweet potatoes underutilized despite their high adaptability and nutritional value. This study used a Participatory Action Research (PAR) approach to assess changes in knowledge, behavior, and community empowerment among 20 members of the Pangan Sentosa Women Farmers Group (KWT) following training on the SIPULUNG sack-based sweet potato cultivation system. The program resulted in notable improvements: knowledge increased by 70%, participation by 75%, goal achievement by 80%, behavioral change by 75%, and environmental impact indicators by 75%. These findings show that SIPULUNG strengthens community capacity in urban settings and aligns with SDG 2 and SDG 12 through sustainable, low-land, low-chemical practices. The group is positioned to pioneer an innovative model of community food security that supports broader national food resilience.